Transient Analysis of Donor-like Surface Traps in GaN HEMTs - Amirali Chalechale; Majid Shalchian; Farzan Jazaeri (AUT Journal of Electrical Engineering, 2022)
Charge trapping in Gallium Nitride-based devices affect their reliability and performance. In this paper, we study the dynamics of charge capture and emission in donor-like surface traps, and the impact of trapped charges on transient response of the drain current in Gallium Nitride High Electron Mobility Transistors (GaN HEMTs). To simulate transient characteristics, traps are excited into their empty or filled state by applying initial pulse on the gate (gate-lag technique) or on the drain (drain-lag), and later the drain current is monitored during transition toward steady state condition. The results show up to 44% variation in drain current level, which reflects the importance of trapped charges in the device characteristics. The effect of physical parameters, including trap energy level and temperature, have been characterized using gate and drain-lag. A simple physical model is proposed (based on the Arrhenius relation) and calibrated with the simulation results to obtain the emission and capture time-constants. The results extracted from the physical model show that the time constant for capture and emission varies from few microseconds to few seconds depending on temperature and trap energy level, and the result are in good agreement with TCAD simulations. This is an important step toward incorporation of charge trapping effect into the charge-based compact model of GaN HEMTs.